2003
DOI: 10.1097/01.rli.0000063983.86229.f2
|View full text |Cite
|
Sign up to set email alerts
|

F-18 Fluorodeoxyglucose Positron-Emission Tomography in the Diagnosis of Tumor Recurrence and Metastases in the Follow-Up of Patients With Breast Carcinoma

Abstract: F-18 FDG PET demonstrates apparent advantages in the diagnosis of metastases in patients with breast carcinoma, compared with conventional imaging on a patient base. On a lesion base, significantly more lymph node and less bone metastases can be detected by using F-18 FDG PET compared with conventional imaging, including bone scintigraphy. In patients with clinical suspicion but negative tumor marker profile, too, F-18 FDG PET seems to be a reliable imaging tool for detection of tumor recurrence or metastases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
1
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(73 citation statements)
references
References 11 publications
4
59
1
7
Order By: Relevance
“…The overall relatively low combined PET/CT sensitivity for this group was because neither CT alone nor combined PET/CT could detect osteogenic bone metastasis that was only detected by bone scintigraphy. This agrees with Gallowitsch et al [16] who found that although PET provided better lesion-based specificity, it exhibited poorer sensitivity for the detection of bone metastases (specificity 88.9%, sensitivity 56.5%) than bone scintigraphy (specificity 74.1%, sensitivity 89.8%). PET yielded a large proportion of false-negative lesions in cases with bone metastasis, and most of the lesions that were not detected by PET were osteogenic or mixed osteogenic/ osteolytic lesions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The overall relatively low combined PET/CT sensitivity for this group was because neither CT alone nor combined PET/CT could detect osteogenic bone metastasis that was only detected by bone scintigraphy. This agrees with Gallowitsch et al [16] who found that although PET provided better lesion-based specificity, it exhibited poorer sensitivity for the detection of bone metastases (specificity 88.9%, sensitivity 56.5%) than bone scintigraphy (specificity 74.1%, sensitivity 89.8%). PET yielded a large proportion of false-negative lesions in cases with bone metastasis, and most of the lesions that were not detected by PET were osteogenic or mixed osteogenic/ osteolytic lesions.…”
Section: Discussionsupporting
confidence: 91%
“…After treatment, follow-up examinations are required for the early detection and accurate staging of recurrences. [2] FDG PET has high accuracy for the diagnosis of recurrent or metastatic breast cancer; FDG PET provides functional information, and it often complements conventional imaging modalities, which are more dependent on morphologic changes to depict disease recurrence. FDG PET is particularly useful for discriminating between viable tumor and post-therapy changes such as necrosis or fibrotic scarring in patients with equivocal results of anatomic imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-specific tracers such as 18 F-FDG and 11 C/ 18 Fcholine reflect underlying metabolic changes in cancer, and it is assumed that most of the signal derives from the tumor cells themselves and that in skeletal metastases there is little, if any, contribution from bone cells. We and others have also noted in the past that 18 F-FDG PET appears to be less sensitive for detecting sclerotic metastases in breast cancer (6,7). A low sensitivity, compared with 99m Tcmethylene diphosphonate scintigraphy (8) or 18 F-fluoride PET (9), has also been noted in prostate cancer, in which bone metastases are predominantly osteoblastic.…”
Section: See Page 176mentioning
confidence: 80%
“…Computer aided diagnosis are more accurate and holds a lot of demand in recent years [6]. Different types of Computer aided diagnosis methods are Computed Tomography [10], Magnetic Resonance Imaging [9], Mammography, Ultrasonography [8], Positron emission Tomography [7] which are developed for easy diagnosis for the different types of lesion. Imaging techniques are used to diagnose various types of cancers in the pelvic region of human female.…”
Section: Introductionmentioning
confidence: 99%